Islamic Values-Oriented Mathematical Physics Module: Design, Validity, Practicality - Nasir, Muhammad; Mawaddah, Sri; Akbar, Rian (Universitas Islam Negeri (UIN) Mataram, 2023)
Mathematical physics has been known as a complex subject for most students to understand. The Islamic values-oriented mathematical physics module was developed to support students learning independently and help them improve intellectually and spiritually in mathematical physics courses. This research aimed to determine the Islamic values-oriented mathematical physics module's development process, validity, and practicality. This research is R&D based on the 4D model, which consists of four steps, namely define (needs analysis and curriculum review), design (module design), develop (module validation with material, media, and tafsir expert validators), and disseminate (student and lecturer responses test). Two aspects related to the developed module are identified: validity and practicality. The validity aspect is obtained from the assessment results by expert validators. Meanwhile, the practicality aspect was obtained from the responses from the lecturers and students who took the mathematical physics course. The novelty of the research is integrating Islamic values into the mathematical physics module so students can improve intellectual and spiritual aspects. The results of the assessment by the expert validator show that the Islamic-values-oriented mathematical physics module is valid and practical to use, with a percentage of assessment by material experts of 94% (excellent), assessment by media experts of 92% (very valid), and assessment by tafsir experts 97% (perfect). Meanwhile, the students' evaluation of the practicality of the module was 96% (efficient), and the evaluation by the lecturers was 97% (efficient). Further researchers are advised to develop research results by involving more research subjects with physics education students from other universities.